Percutaneous Trapeziometacarpal Arthrodesis in Thumb Carpometacarpal Joint Arthritis: A New Surgical Approach - D. Mifsut-Miedes; J. R. Rodríguez-Collell; A. Valverde-Navarro; E. M. González-Soler (Case Reports in Orthopedics)
The high prevalence of trapeziometacarpal arthritis has resulted in the development of several surgical techniques intended to treat patients failing conservative treatment. However, there is no scientific evidence of the superiority of one technique over others. Open arthrodesis has up to now been successfully used to treat this condition. We believe that performing the technique using a minimally invasive approach with long and short Shannon burrs together with the tapered burr included in the MIS foot instrument set can yield satisfactory results. This article provides a description of this minimally invasive technique performed on a seventy-year-old woman with rhizarthrosis and an anatomical description of the approach in a human cadaver.